Evolution of thermal tolerance in multifarious environments. Issue 22 (24th October 2018) - Cuenca Cambronero, Maria; Beasley, Jordan; Kissane, Stephen; Orsini, Luisa
Abstract: Species extinction rates are many times greater than the direst predictions made two decades ago by environmentalists, largely because of human impact. Major concerns are associated with the predicted higher recurrence and severity of extreme events, such as heat waves. Although tolerance to these extreme events is instrumental to species survival, little is known whether and how it evolves in natural populations, and to what extent it is affected by other environmental stressors. Here, we study physiological and molecular mechanisms of thermal tolerance over evolutionary times in multifarious environments. Using the practice of "resurrection ecology" on the keystone grazer Daphnia magna, we quantified genetic and plastic differences in physiological and molecular traits linked to thermal tolerance in historical and modern genotypes of the same population. This population experienced an increase in average temperature and occurrence of heat waves, in addition to dramatic changes in water chemistry, over five decades. On genotypes resurrected across the five decades, we measured plastic and genetic differences in CTmax, body size, Hb content and differential expression of four heat shock proteins after exposure to temperature as single stress and in combination with food levels and insecticide loads. We observed evolution of the critical thermal maximum and plastic response in body size, HSP expression and Hb content over time in a warming only scenario. Molecular and physiological responses to extreme temperature in multifarious environments were not predictable from the response to warming alone. Underestimating the effect of multiple stressors on thermal tolerance can lead to wrong estimates of species evolvability and persistence.